1997
DOI: 10.1046/j.1365-2249.1997.4631361.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytokine gene expression by adjuvants in vivo

Abstract: Antibody isotype affects biological activity of the antibodies and therefore should be considered in prevention of disease by vaccination. In previous reports, we demonstrated that adjuvants affect the antibody isotype switching process and favour the production of certain isotypes. The present study extends these findings and shows fundamental differences in the cytokine induction pattern according to the adjuvant used. Cytokine mRNA levels were determined by in situ RNA–RNA hybridization performed on splenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
8

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 36 publications
2
32
0
8
Order By: Relevance
“…It was previously shown that the induction of a Th2 T cell response depends on the balance between both IL-4 and INF-␥ (Victoratos et al, 1997). We observed here that despite the moderate increase in IL-10 secretion, the increase in levels of IFN-␥ is more pronounced, indicating a balance favoring a Th1-type response.…”
Section: Discussionsupporting
confidence: 54%
“…It was previously shown that the induction of a Th2 T cell response depends on the balance between both IL-4 and INF-␥ (Victoratos et al, 1997). We observed here that despite the moderate increase in IL-10 secretion, the increase in levels of IFN-␥ is more pronounced, indicating a balance favoring a Th1-type response.…”
Section: Discussionsupporting
confidence: 54%
“…Generally, the affinity of an antibody varies in the participating cells and cytokines in a dependent manner [39][40][41] . It is well known that a TI response, one of the natural defense mechanisms of a host to remove invading antigens, can be characterized by the rapid production of "low avidity" IgM 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is important in host defense against foreign invaders such as bacteria, whereas IL-6 is important in B-cell differentiation, antibody production, and T-cell proliferation and activation (Akira et al, 1990). IL-6 and TNF-α levels are elevated following exposure to bacterial endotoxins such as lipopolysaccharide (LPS) (Victoratos et al, 1997).…”
Section: Introductionmentioning
confidence: 99%